MORPHOLOGICAL AND MORPHOMETRIC CHANGES OF THE THYMUS IN 2-MONTH-OLD ALBINO RATS UNDER CHEMOTHERAPY (Ideal Journal of Multidisciplinary Research, 2026)
Chemotherapy, while effective in cancer treatment, may negatively affect immune organs, including the thymus, which is essential for T-lymphocyte maturation and immune regulation. This study aimed to evaluate morphological and morphometric changes in the thymus of 2-month-old albino rats following chemotherapy exposure. Histological and morphometric analyses assessed alterations in the thymic capsule, trabeculae, vascular structures, and cellular composition. The results demonstrated significant thinning of the thymic capsule in gateway, anterior, and posterior regions compared with controls, accompanied by fiber loosening, focal destruction, and vacuole formation between collagen fibers. Trabeculae showed decreased thickness and length, as well as disorganization of collagen architecture. Morphometric evaluation revealed reduced arteriolar and venular wall thickness, indicating vascular alterations under chemotherapeutic influence. Additionally, a marked reduction in thymocyte proportion and lymphocyte number was observed in both cortical and medullary layers. These findings indicate disruption of the thymic microenvironment and suggest decreased functional activity of the organ following chemotherapy. Overall, the study highlights the susceptibility of the thymus to cytotoxic treatment and the importance of monitoring thymic integrity during chemotherapy.
Keywords: Thymus, chemotherapy, morphometry, thymic capsule, trabeculae, albino rats, histological changes.